Mechanical mapping of mammalian follicle development using Brillouin microscopy - Chan, Chii Jou; Bevilacqua, Carlo; Prevedel, Robert (Communications biology, 2021)
In early mammalian development, the maturation of follicles containing the immature oocytes is an important biological process as the functional oocytes provide the bulk genetic and cytoplasmic materials for successful reproduction. Despite recent work demonstrating the regulatory role of mechanical stress in oocyte growth, quantitative studies of ovarian mechanical properties remain lacking both in vivo and ex vivo. In this work, we quantify the material properties of ooplasm, follicles and connective tissues in intact mouse ovaries at distinct stages of follicle development using Brillouin microscopy, a non-invasive tool to probe mechanics in three-dimensional (3D) tissues. We find that the ovarian cortex and its interior stroma have distinct material properties associated with extracellular matrix deposition, and that intra-follicular mechanical compartments emerge during follicle maturation. Our work provides an alternative approach to study the role of mechanics in follicle morphogenesis and might pave the way for future understanding of mechanotransduction in reproductive biology, with potential implications for infertility diagnosis and treatment.
Gesehen am 17.11.2021